Respostas
respondido por:
1
2(x+5)+4 (x-1)=0
2x+10+4x-4=0
2x+4x=-10+4
6x=-6
x=-1
Giovanna46799:
obgd❤
respondido por:
2
Olá!!!
Resolução!!!
2 ( x + 5 ) + 4 ( x - 1 ) = 0
2x + 10 + 4x - 4 = 0
2x + 4x = 4 - 10
6x = - 6
x = - 6/6
x = - 1
S = { - 1 }
Espero ter ajudado!!!
Resolução!!!
2 ( x + 5 ) + 4 ( x - 1 ) = 0
2x + 10 + 4x - 4 = 0
2x + 4x = 4 - 10
6x = - 6
x = - 6/6
x = - 1
S = { - 1 }
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás